OS 01-04 WHOLE BLOOD VISCOSITY WAS ELEVATED IN PATIENTS WITH BOTH HYPERTENSION AND ACUTE CORONARY SYNDROME. (September 2016) - Song, Soo-Kyeong; Lee, Sang-Rok; Jung, Lae-Young; Kim, Yi-Shik; Lee, Sun-Hwa; Rhee, Kyoung-Suk; Chae, Jei-Keon; Kim, Won-Ho; Ko, Jae-Ki
Abstract : Objective: Wall shear stress contributes to atherosclerosis progression and plaque rupture. There were limited studies for hypertension as influence factor on whole blood viscosity (WBV) in acute coronary syndrome (ACS) patients. We evaluated the relations between WBV and hypertension in patients who visited to the emergency room by acute chest pain. Design and Method: From April 2013 through June 2015, we prospectively enrolled 471 acute chest pain patients who visited emergency room. We divided study population as two groups according to the presence of hypertension, group A (257 patients with hypertension, mean age 64.25 ± 9.44 years) and group B (214 patients without hypertension, mean age 60.16 ± 11.12 years). WBV at shear rates of 1 s −1 (diastolic blood viscosity; DBV) and 300 s −1 (systolic blood viscosity; SBV) were measured by by a scanning capillary tube viscometer (Bio-Visco Inc., South Korea). Results: There was no significant difference in baseline clinical characteristics between the two groups. Both systolic blood viscosity (group A: group B = 43.08 ± 7.24: 42.38 ± 6.39 mP, p = 0.02) and diastolic blood viscosity (281.11 ± 68.61: 276.16 ± 70.06 mP, p = 0.04) were higher in group A. In a receiver operating characteristic curve analysis, systolic blood viscosity value of 42.05 mP (sensitivity 0.533, specificity 0.537) and diastolic blood viscosity value of 274.85 mP (sensitivity 0.547, specificity 0.542) were identified as an effective cut-point in the discrimination of the hypertension. After correction of traditional cardiovascular risk factors (i.e., diabetes, dyslipidemia, smoking, stroke), there was still mild association between diastolic blood viscosity and ACS (OR 1.003, p = 0.03). Conclusions: There was a positive association between WBV and hypertension. We provided reference values for WBV in patients with hypertension. Future larger study would be needed to clarify our results.